Capability of silicon carbide schottky diodes as radiation detector and for X-ray photon energy harvesting - Nurul Syazwina Mohamed
Silicon carbide (SiC) offers a response that is closer to human tissue in comparison to high atomic number semiconductor materials and is highly radiation tolerant in a wide range of applications including space exploration, nuclear decommissioning and medical applications. Investigations to the radiation performance of SiC have been reported by a number of research groups aspiring to invent new detectors with a view to monitoring dose rates across a wide dose rate range, but few have reported low dose rate measurements that are suitable for medical applications. Accurate knowledge of the dose rate is imperative in medical treatment. which involves both imaging and radiotherapy. where a wide range of dose rates and energies are used. primarily comprising photonic radiation. Thereforc. this project investigated the suitability of 4H-SiC Schottky diodes as radiation detectors for medical applications. which involved low and high dose rate range. as well as the first demonstration of an X-ray photon energy harvester capable of powering a wireless sensor node. The initial phase of the study involved optimization of the fabrication and parametric characterisation of Schottky diode based on Ni2Si. Current-voltage (I-V) characteristics utilising forward and reverse bias voltages were used to determine the specific on resistance, Ron. ideality factor. II. barrier height. b and leakage current. The diodes showed outstanding characteristics in terms of the extracted ideality factor and barrier height at room temperature and these showed minimal variation with temperature for measurements below 100°C. indicating the formation of a high-quality metal¬semiconductor interface. Valuable insights on the capability of the fabricated Schottky diodes to exposure to low dose rate X-ray photons in terms of the linearity and dose rate sensitivity at room and elevated temperatures have been presented. Detectors were exposed to X-ray photons from a tungsten tube operating with an accelerating bias of 35 kV using a Phywe Xpert4 system operating with tube currents between 0.2 and 1.0 mAo The generated current signal was linearly dependent on the volume of the space charge region formed under the Schottky contact and revealed a sensitivity which is a factor of 106 higher than that reported in the literature. The temperature dependence of the characteristics indicated that SiC Schottky diode-based detectors offer a performance suitable for medical applications at temperatures below 100°C without the need for external cooling. The correlation of diode electrical characteristics with the spectroscopic response when exposed to a 211 Am alpha source and the performance capabilities as an X-ray photon energy harvester was investigated. Spectroscopic characterisation revealed detector 05 with the highest energy resolution in the range of 0.084 % and O. I 33 % for bias voltages between 0 and -40 Y, in comparison to the other two detectors. Additionally, the leakage current of detector 05 which was < I nAicm2 for biases below -50 Y, that demonstrated a significantly lower noise spectral density, with a current dependence f3 = 3. I 6, was demonstrated to be the most suitable for use as a X-ray photon energy harvester. This confirms the possibility of scavenging energy from an X-ray beam and the capability of developing a self-powered system using silicon carbide technology for deployment in extreme environments. The final phase of this project involved the response of the selected detector (02) to high energy (6 MY) photon irradiation as a function of cumulative dose to a maximum of 1000 Gy. The realization of a vertical detector structure, coupled with the high quality of epitaxial layers, has resulted in a high dose sensitivity of the detector that is highly linear for all bias voltages used in the study. In addition, the effect on the characteristics properties and performance capabilities in terms of X-ray photon energy harvester before and after the high-energy irradiation was analysed. The specific on resistance, ideality fucror and barrier height demonstrated insignificant changes after exposure to a cumulative dose of 1000 Gy, whilst the dopant concentration and depletion width based on the C¬Y measurements were observed to decrease by approximately I I % and 17% (at typically -30 Y), respectively. In summary, the realization of dosi meters with enhanced sensitivity for a wide range of incident dose rates is feasible with silicon carbide technology. opening up the possibility of radiation monitoring for long periods in extreme environments. Furthermore, it is possible to power a wireless sensor node. comprising the power converter, signal conditioning and sensor manufactured from silicon carbide, from incident radiation with a dose rate comparable to that found in conventional medical systems.